Planning and Design of a Coffee Peeling Machine with a Capacity of 100 Kg/Hour - Rahman, Hidayatur; Abu, Risal; Mukhnizar, Mukhnizar; Koto, Rahmat Desman (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
This research aims to design a coffee peeling machine with a capacity of 100 kg/hour to improve the efficiency and effectiveness of the coffee peeling process, which is currently done manually by Indonesian farmers with limited results. The machine is equipped with a motor, V-belt, pulley, peeling rollers, and a hopper. Test results show an average peeling time of 35 seconds per kilogram, with a capacity of 102.8 kg/hour and an efficiency of 95%. Its innovative design prevents coffee bean buildup, ensures smooth flow, and is easy to use and maintain. This machine not only enhances productivity and coffee quality but also reduces labor costs. By using this machine, farmers can speed up the peeling process and be more efficient in meeting market demands. Further development is recommended to improve material quality, optimize the design, and provide training for farmers on machine use. Penelitian ini merancang mesin pengupas kulit kopi berkapasitas 100 kg/jam untuk meningkatkan efisiensi dan efektivitas pengupasan kopi, yang selama ini dilakukan secara manual oleh petani di Indonesia dengan hasil yang terbatas. Mesin ini dilengkapi motor penggerak, V-belt, pulley, roller pengupas, dan hopper. Hasil pengujian menunjukkan waktu pengupasan rata-rata 35 detik per kilogram dengan kapasitas 102,8 kg/jam dan efisiensi sebesar 95%. Desain inovatifnya mencegah penumpukan biji, memastikan aliran yang lancar, serta mudah digunakan dan dirawat. Mesin ini tidak hanya meningkatkan produktivitas dan kualitas kopi, tetapi juga mengurangi biaya tenaga kerja. Dengan penggunaan mesin ini, petani dapat mempercepat proses pengupasan dan lebih efisien dalam memenuhi permintaan pasar. Pengembangan lebih lanjut disarankan untuk meningkatkan kualitas material, optimasi desain, dan pelatihan penggunaan bagi petani.